Portable Bioactive Paper-Based Sensor for Quantification of Pesticides - Murat Kavruk; Veli Cengiz Özalp; Hüseyin Avni Öktem (Journal of Analytical Methods in Chemistry)
A paper-based biosensor was developed for the detection of the degradation products of organophosphorus pesticides. The biosensor quantifies acetylcholine esterase inhibitors in a fast, disposable, cheap, and accurate format. We specifically focused on the use of sugar or protein stabilizer to achieve a biosensor with long shelf-life. The new biosensor detected malathion with a detection limit of 2.5 ppm in 5 min incubation time. The operational stability was confirmed by testing 60 days storage at 4°C when glucose was used as stabilizer.